FANDOM


a = b
a^2 = ab
a^2 - b^2 = ab - b^2
(a - b)(a + b) = b(a - b)
(a - b)(a + b) = b(a - b)
(a + b) = b
but a = b
therefore:
a + a = a
2a = a
hence
2 = 1

there is a calculus version of the equation which may be done later.

Ad blocker interference detected!


Wikia is a free-to-use site that makes money from advertising. We have a modified experience for viewers using ad blockers

Wikia is not accessible if you’ve made further modifications. Remove the custom ad blocker rule(s) and the page will load as expected.